2014
DOI: 10.1007/s00281-014-0430-z
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for B cell targeting in SLE

Abstract: B cells are central pathogenic players in Systemic Lupus Erythematosus and multiple other autoinmune diseases through antibody production as well as antibody independent functiona. At the same time, B cells are known to play important regulatory functions that may protect against autoimmune manifestations. Yet, the functional role of different B cell populations and their contribution to disease remain to be understood. The advent of agents that specifically target B cells, in particular anti-CD20 and ant-BLyS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…It is known that B lymphocytes are involved in the pathogenesis of systemic lupus erythematosus (SLE) in autoantibody-dependent mechanisms. While some recent studies suggested that autoantibody-independent mechanisms might be more important, the specific mechanism is still unclear [35]. Investigations in the MRL/ lpr mouse model of lupus nephritis have indicated that B cells exert a pathogenic role in the absence of soluble autoantibody production [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that B lymphocytes are involved in the pathogenesis of systemic lupus erythematosus (SLE) in autoantibody-dependent mechanisms. While some recent studies suggested that autoantibody-independent mechanisms might be more important, the specific mechanism is still unclear [35]. Investigations in the MRL/ lpr mouse model of lupus nephritis have indicated that B cells exert a pathogenic role in the absence of soluble autoantibody production [6].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal B cell activation contributes to SLE pathogenesis through both antibody-dependent and independent fashions [1, 54, 7981]. In addition to the impaired B cell survival, B cell-specific deletion of PKK also resulted in significant reduction of activated CD4 + T cells in Sle mice (Figure 5), and PKK-deficient Sle B cells fail to efficiently up-regulate the critical T cell-costimulatory molecules CD80 and CD86 in response to BCR stimulation (Figure 6C).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that B cells play a central role in autoimmune diseases through their unique functions including auto-antibody production and antibody-independent functions such as antigen presentation to T cells and cytokine production [16]. The deregulation of B cell development pathways, such as alterations in B cell receptor (BCR) signaling, can lead to the development of lupus [711].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-CD20 mAbs efficiently deplete mature naïve and memory B cells [36]. However, B cells in the early developmental stages, as well as the majority of plasma cells, are largely resistant to depletion by anti-CD20 because these B-cell subsets do not express detectable CD20 on the cell surface [36].…”
Section: Rationale For Targeting Cd19 and The Development Of Inebimentioning
confidence: 99%
“…However, B cells in the early developmental stages, as well as the majority of plasma cells, are largely resistant to depletion by anti-CD20 because these B-cell subsets do not express detectable CD20 on the cell surface [36]. In contrast, CD19 has a broader expression during B-cell development than does CD20 [37,38].…”
Section: Rationale For Targeting Cd19 and The Development Of Inebimentioning
confidence: 99%